Juventude e participação política no Brasil : efeitos de ciclos de vida ou geração? - Okado, Lucas Toshiaki Archangelo (2014)
The academic debate about political participation, and even common sense, has pointed to a possible removal of youth from public issues. This has been evidenced mainly by the fall in repertoires of conventional participation, related to activism linked traditional institutions of democracy, especially political parties and turnout. This means that the youth has been discharged from participating in public life in many countries of America and Europe. In this context two theories have tried to explain the meanings of this phenomenon: the first, linked to the Theory of Human Development proposed by Rolnald Inglehart and colleagues have associated this incident to the process of generational overlap. High levels of income, education and quality of life provided the change of individual priorities, emphasizing the values of self-expression. These values are associated with more critical democratic institutions, even the owners of these to support a greater number, which has shifted the activism of younger generations to unconventional participation. Young people, more susceptible to this effect, would be migrating to other forms of participation, notably the protest actions. Meanwhile, another theory attempts to explain this phenomenon through the inherent changes in the life cycle, attributing this difference in participation between youth and adults the changes that occur in the course of individual's bibliography, especially the transition from youth to adulthood. This study examined the impact of these two theoretical perspectives on the activism of young Brazilian. Through a longitudinal analysis that takes into account effects of life cycle, generational overlap and period, it was found, for the Brazilian context, youth participation is strongly mediated by the effects of the life cycle.